Collective action for equitable natural resource management in Eastern African highlands - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Despite an increased awareness of the institutional foundations of development and natural resource management, development interventions continue to have a strong technological bias. Development and conservation interventions continue to be carried out with an uncritical view to equity or the possible negative repercussions on certain social groups, or on environmental sustainability. Local institutions (rules and structures) remain largely invisible to outside actors. However, the shortcomings lie not only with practitioners, but also within research which, on the institutional dimensions of development and NRM, continues to emphasize problems rather than solutions. One way of addressing these shortcomings is by integrating institutional analysis for problem identification and targeting of interventions with action research in the form of institutional interventions for development of good practice.